Disparities in Caries Experience and Socio-Behavioural Risk Indicators Among Private School Children in Lagos, Nigeria - Olubukola Olamide Olatosi; Afolabi Oyapero; Nneka Kate Onyejaka (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the prevalence and socio-behavioural risk factors for dental caries among children at selected LGAs in Lagos State. Material and Methods: This was a descriptive study of 592 school children in four Local Government Areas of Lagos, Nigeria. The presence of caries was recorded using the World Health Organization criteria. Descriptive statistics were reported for analysis of comparative DMFT and SiC scores in relation to age, gender, and other socio-demographic variables.  Logistic  regression analysis was used to analyze the differential impact of the variables on the probability of being in the high caries prevalence group. Results: The prevalence of dental caries was 16.0% with mean dmft for age 6 being 1.3 ± 1.57 while the mean DMFT for age 12 was 0.15 ± 0.67. The mean Sic for age 6 was 1.5 ± 0.53 while the mean SiC for age 12 was 1.09 ± 0.29. The mean SiC values was significantly higher in the primary and permanent dentition among those who had never visited the dentist, female students, those who don't use fluoridated toothpaste and those who eat sweets and candy several times a day. After logistic regression analysis, those with no previous dental visit (OR=3.05; CI: 1.72-4.67) and females (OR=1.55; CI: 1.16-1.62) still had significantly higher SiC Values. Conclusion: The prevalence of caries was low in the study population. Being female, non-use of fluoride-containing toothpaste and not visiting the dentist were significant predictors of dental caries among children attending private schools.